Program pendidikan Islamic Worldview untuk murid SMA Boarding School - Dhohir, Irfan Ilahi; Tamam, Abas Mansur; Supraha, Wido (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
This study aims to formulate an Islamic Worldview education program for dormitory-based high school students in order to form a comprehensive and solid Islamic understanding in the midst of the challenges of the times. A qualitative approach is used with data collection techniques through literature studies, field observations, in-depth interviews, and forum group discussions (FGDs). The concept of Islamic Worldview developed by Syed Muhammad Naquib al-Attas in the work “Prolegomena to the Metaphysics of Islam” became the main foundation in the formulation of this program. Field studies at Pesantren At-Taqwa Depok were used to strengthen the validity of the formulated concept. The results showed that the internalization of Islamic Worldview in education is very important in fortifying students from the influence of liberal ideology and moral deviation. The proposed program includes activities such as book sharing, book studies, Islamic discussions, and insight enhancement forums designed to foster students' critical and spiritual awareness. The conclusion of this study emphasizes the need for integration of Islamic values in adolescent education as a strategy to face global challenges. Abstrak Penelitian ini bertujuan untuk merumuskan program pendidikan Islamic Worldview bagi murid sekolah menengah atas berbasis asrama dalam rangka membentuk pemahaman keislaman yang komprehensif dan kokoh di tengah tantangan zaman. Pendekatan kualitatif digunakan dengan teknik pengumpulan data melalui studi pustaka, observasi lapangan, wawancara mendalam, dan Forum Group Discussion (FGD). Konsep Islamic Worldview yang dikembangkan oleh Syed Muhammad Naquib al-Attas dalam karya